Proses Komunikasi Intrapersonal Untuk Meningkatkan Self Worth Setelah Mengalami Toxic Relationship Pada Perempuan Dewasa - Namira Fitria (Brand Communication, 2023)
The purpose of this study was to determine the process of intrapersonal communication to increase self worth after experiencing a toxic relationship in adult women. Intrapersonal communication which is a process of thinking by talking to oneself to contemplate how valuable and qualified we are so that self-confidence will arise. Thus a good self worth will arise in a person. The victims of toxic relationships are generally rooted in not having good self worth, they are not aware that they are valuable and do not deserve to be treated badly. The research method used is a qualitative approach. Data collection techniques are FGD, observation, and in-depth interviews with informants/participants as primary data. Meanwhile, secondary data uses literature studies sourced from journals, e-books/books and documents. The data analysis technique uses the Miles & Huberman Interactive Model. The results of this study indicate that through the process of intrapersonal communication it is able to increase good self worth thereby preventing toxic relationships from reoccurring.